Systemic Outcomes of (Pyr(1))-Apelin-13 Infusion at Mid-Late Pregnancy in a Rat Model with Preeclamptic Features - Yamaleyeva, Liliya M. (Sci Rep, 2019)
Preeclampsia is a syndrome with diverse clinical presentation that currently has no cure. The apelin receptor system is a pleiotropic pathway with a potential for therapeutic targeting in preeclampsia. We established the systemic outcomes of (Pyr(1))-apelin-13 administration in rats with preeclamptic features (TGA-PE, female transgenic for human angiotensinogen mated to male transgenic for human renin). (Pyr(1))-apelin-13 (2 mg/kg/day) or saline was infused in TGA-PE rats via osmotic minipumps starting at day 13 of gestation (GD). At GD20, TGA-PE rats had higher blood pressure, proteinuria, lower maternal and pup weights, lower pup number, renal injury, and a larger heart compared to a control group (pregnant Sprague-Dawley rats administered vehicle). (Pyr(1))-apelin-13 did not affect maternal or fetal weights in TGA-PE. The administration of (Pyr(1))-apelin-13 reduced blood pressure, and normalized heart rate variability and baroreflex sensitivity in TGA-PE rats compared to controls. (Pyr(1))-apelin-13 increased ejection fraction in TGA-PE rats. (Pyr(1))-apelin-13 normalized proteinuria in association with lower renal cortical collagen deposition, improved renal pathology and lower immunostaining of oxidative stress markers (4-HNE and NOX-4) in TGA-PE. This study demonstrates improved hemodynamic responses and renal injury without fetal toxicity following apelin administration suggesting a role for apelin in the regulation of maternal outcomes in preeclampsia.